Preparation and characterization of lead-free (Ba0.4Sr0.4Ca0.2)(Zr0.05Ti0.95)O3ceramics using BST seed induced method - Jiraporn Dangsak (2018)
© 2018 Trans Tech Publications, Switzerland. The solid solution of lead-free (Ba0.4Sr0.4Ca0.2)(Zr0.05Ti0.95)O3(BSCZT) ceramics were prepared from the seed induced method. The Ba0.6Sr0.4TiO3(BST) were used as the seed crystals, they were prepared using the molten salt technique. The phase formation was examined using the X-ray diffraction technique (XRD). It was found that the single phase perovskite structure of BST was obtained at a temperature of 800°C. The ceramics were prepared using the conventional solid state reaction by adding of BST seed crystals at 2.5, 5, 7.5 and 10 mol%. The structure showed that a single phase perovskite was obtained after sintered at 1400 °C. This work confirmed that BST seed crystal successfully diffused into BSCZT ceramic and the BSCZT ceramic with a seed crystal showed higher dielectric constant than the BSCZT ceramic without seed crystals.